1998
DOI: 10.1104/pp.116.4.1259
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Plant Host Synthesizes the Heme Moiety of Leghemoglobin in Root Nodules1

Abstract: Although it is well established that the plant host encodes and synthesizes the apoprotein for leghemoglobin in root nodules, the source of the heme moiety has been uncertain. We recently found that the transcript for coproporphyrinogen III oxidase, one of the later enzymes of heme synthesis, is highly elevated in soybean (Glycine max L.) nodules compared with roots. In this study we measured enzyme activity and carried out western-blot analysis and in situ hybridization of mRNA to investigate the levels durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…S3A). The specific activity of this enzyme in nodule was 27-fold higher than that in the uninfected roots, 40) due to the high demand for heme required for the formation of hemoproteins in the nodule. 41) Although Lb is an essential protein in nitrogen fixation, it is also the main source of reactive oxygen species (ROS) in the nodule.…”
Section: Discussionmentioning
confidence: 99%
“…S3A). The specific activity of this enzyme in nodule was 27-fold higher than that in the uninfected roots, 40) due to the high demand for heme required for the formation of hemoproteins in the nodule. 41) Although Lb is an essential protein in nitrogen fixation, it is also the main source of reactive oxygen species (ROS) in the nodule.…”
Section: Discussionmentioning
confidence: 99%
“…B. japonicum can also synthesize heme (13) and export the heme to periplasm by the cycVWX complex for cytochrome c biogenesis (14,39). It has been concluded that the heme of leghemeglobin was mainly derived from plants during nodulation (34,42). It is unlikely that leghemoglobin is a source of heme or Fe 3+ for B. japonicum during symbiosis.…”
Section: Involvement Of Tbdrs In the Iron Uptake Mechanism Of Rhizobamentioning
confidence: 99%
“…In M. loti MAFF303099, the only TBDR sequence is a putative heme/hemoprotein-specific TBDR, implying that the TBDR for Fe 3+ -siderophores is not essential in this bacteria. The synthesis of heme involves multiple steps (19) and both rhizobacteria and plants have this ability (29,42). In plants, a large amount of heme is required for functional a Transcriptomic analyses were carried out on free-living cells growing in PSY medium (OD 0.4-0.5) and on 21-day-old bacteroids.…”
Section: Involvement Of Tbdrs In the Iron Uptake Mechanism Of Rhizobamentioning
confidence: 99%
“…There is now strong evidence that the synthesis of the haem group that is required for the fully functional lehaemoglobin protein is also under the control of plant genes (O'Brian 1996). Five enzymes involved in haem synthesis were shown to increase during the development of soybean nodules (Santana et al 1998). For coprogen oxidase (Madsen et al 1993), the increases in enzyme activity also correlated with mRNA and enzyme protein.…”
Section: The Further Development Of the Nodule Late Nodulinsmentioning
confidence: 96%